Effect of insulin dose adjustment for glycaemic control on body mass index : a retrospective cohort study of type 1 diabetes patients at the Kalafong Diabetic Clinic between 2009 and 2014 - Van Zyl, Danie G. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2016.